On the identity of Amegilla sesquicincta (Erichson) and the type species of Dizonamegilla (Hymenoptera: Apidae). - Engel, Michael S. (Contributions to Entomology = Beiträge zur Entomologie, 2009)
Notes are provided on the identity and nomenclature of Amegilla sesquicincta (Erichson), a name long confused in its application. Amegilla sesquicincta is a Senegalese species of uncertain identity while the species from India to which this name has been applied is preoccupied and accordingly named A. dizona nom. n. As this name was used as the type species of the subgenus Dizonamegilla, the question of the type species for this group is addressed and subsequently fixed as A. dizona in accordance with ICZN regulations. Keywords Nomenclature, Amegilla, Senegal, India, Apidae, Anthophila. Nomenclatural Acts dizoma Engel, 2009 (Amegilla), nom. n. pro Apis bicincta Fabricius, 1793, nec Schrank, 1781 sesquicincta (Erichson, 1842) (Amegilla), nom. dub. described as Megilla sesquicincta bizoma Engel, 2009 (Amegilla (Dizonamegilla)), type species of the subgenus Dizonamegilla